A Frequency-Dependent Hybrid Implicit-Explicit FDTD Scheme for Dispersive Materials - Chen, Juan; Zhang, Anxue (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A frequency-dependent hybrid implicit-explicit finite-difference time-domain (HIE-FDTD) method for dispersive materials is presented. This method has higher computation efficiency than the conventional FDTD method, because the time step in this method is only determined by two space discretizations. The accuracy of this method is demonstrated by computing the incident at a planar air-water interface over a wide frequency band including the effects of the frequency-dependent permittivity of water.